ANALISIS PERAN KOMPENSASI DAN BUDAYA ORGANISASI DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI - Muchtar Habib (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
This research was conducted with the aim of providing a comprehensive understanding of the influence of compensation and organizational culture on employee performance by using a literature review approach. This study collects and analyzes a variety of relevant scientific sources, including national and international journals, academic textbooks, and research results related to human resource management. Data analysis was carried out in a qualitative descriptive manner through a thematic synthesis process. The results of the analysis show that both compensation and organizational culture have a positive and significant influence on employee performance, both partially and simultaneously. Fair compensation, transparency, and contribution has been proven to create work motivation and loyalty, while a constructive organizational culture and harmonious social relationships play an important role in creating work effectiveness and employee satisfaction. Simultaneously, these two variables have a synergistic effect in encouraging the achievement of optimal performance and organizational goals.